1994
DOI: 10.1002/1097-0142(19940401)73:7<1971::aid-cncr2820730731>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Extragonadal germ cell tumors. A 14-year Toronto experience

Abstract: Background. Extragonadal germ cell tumors (EGCT) represent only 2–5% of adult germ cell malignancies. Because they are rare and biologically distinct from testis cancer, their natural history and optimal management continue to be defined. The clinical characteristics, treatment, and outcome of 40 patients are presented here. Methods. Patients were identified through the medical records of four University of Toronto teaching hospitals. All patients were treated in specialized oncology units between 1978 and 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 39 publications
5
35
1
2
Order By: Relevance
“…Primary extragonadal germ cell tumors are uncommon tumors that most often occur in the midline structures and mediastinum, but they can also occur in many other organs, not only in children but also in adults. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Morphologically, primary extragonadal germ cell tumors can mimic many types of non-germ cell tumors. For example, mediastinal seminomas may mimic type B thymomas and embryonal carcinoma may mimic other types of carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Primary extragonadal germ cell tumors are uncommon tumors that most often occur in the midline structures and mediastinum, but they can also occur in many other organs, not only in children but also in adults. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Morphologically, primary extragonadal germ cell tumors can mimic many types of non-germ cell tumors. For example, mediastinal seminomas may mimic type B thymomas and embryonal carcinoma may mimic other types of carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Motzer et al 20 recommended resection of residual tumors to prevent disease recurrence and to confirm the effects of chemoradiation therapy, which corresponded with our own experience. Goss et al 21 concluded that patients with mediastinal seminomas have an excellent outcome regardless of the treatment approach. The role of surgical resection is changing.…”
Section: Seminomasmentioning
confidence: 99%
“…Often it's difficult for clinicians distinguish primary germ cells tumour to metastatic lesion specially for seminoma, which tend to spread by lymphatic channel to retroperitoneal lymph nodes. Previous reports in literature described a "burned out" phenomenon of germ cells tumours, consisting in extragonadal germ cell tumour with no evidence of neoplasm at the testis level [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%